Study on electrochemical mechanical polishing process of silicon carbide crystal - Lei WANG; Runze WU; Lin NIU; Zhibo AN; Zhuji JIN (Jin'gangshi yu moliao moju gongcheng, 2022)
To solve the problem of low polishing efficiency of silicon carbide crystal, electrochemical mechanical polishing (ECMP) of silicon carbide was carried out to study the effect of NaOH, NaNO3 and H3PO4 electrolytes on electrochemical oxidation of silicon carbide. NaNO3 of 0.6 mol/L was selected as the electrolyte in the ECMP process and so were the diamond-alumina mixed abrasive particles. The influence of load, rotational speed, voltage and particle size on the surface quality and material removal rate of ECMP silicon carbide was studied by using orthogonal experiment. With the optimized processing parameters, the combined polishing experiment can achieve a high-efficiency material removal rate of 20.259 μm/h in the rough polishing stage, and finally obtain the surface roughness of Sa 0.408 nm through precision polishing.